WOMEN’S STRUGGLE TO ACHIEVE THEIR GENDER EQUALITY IN PRIDE AND PREJUDICE AND JURNAL PH.D MAMA: A COMPARATIVE STUDY - Olga A. Rorintulus; Imelda Lolowang; Aprillya Alwien Suoth; devilito tatipang; Pritania Mokalu; Blessy Wilar; Geral Pratasik (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Women’s struggle to achieve their gender equality in Pride and Prejudice (1813) and Jurnal P.hD Mama (2019) were showed clearly. Interestingly, since in Regency Period until this time, women needed extra effort to achieve their gender equality or to struggle even for their rights in life. This study aimed to compare and reve al the women’s struggle to achieve their gender equality in Pride and Prejudice and Jurnal P.hD Mama. This article used qualitative method, and applied feminist literary approach. The data are collected from primary and secondary sources. The primary sources were the novel entitled Pride and Prejudice written by Jane Austen and Jurnal P.hD Mama written by Kanti Pertiwi et.al. The second sources were some related books and articles that are supporting this study. The result of this study was revealing women’s struggle that happened in the novels and the reasons behind it since Regency Period (1795-1837) and still suitable until this modern era. Indirectly, this study reveals the position of gender equality. It could be reality or dream. This study show how gender could influence human to achieve their rights. There was gap and no equal between man and woman. Gender equality had become a concept that is difficult to achieve. This study also has great significances to ELT, especially in education field. Teacher and student should have the right perspective about gender equality, so in the process of learning, gender could not become boundary to human in gain knowledge and social skill